Survey of job dimensions and professional requirements of special librarians in Metropolitan Manila - Barnachea, Lutgarda Amor D. (1989)
This study aimed to conduct a survey of the job dimensions and professional requirements of special librarians. Respondents were 51 librarians working in different types of special libraries located in Metropolitan Manila. The instrument used in the study is a questionnaire which asked for the following information: personal and career information, job activities performed in terms of time and importance, and professional needs of librarians. Analysis of data used frequency counts, sums, products, percentages and ranking.